Use of Flyash and Plastic Waste as a Constituent in Concrete (International Journal of Innovative Research in Engineering & Management, 2023)
Cement production gives rise to CO2 emissions generated by calculations of CaCO3 and by  fossil, being responsible for about 5% of the CO2 emissions  in the world. This can be substantially reduced if cement  replacement materials, either partial or complete such as fly  ash are used. Presently large amounts of fly ash are  generated in thermal industries with an important impact on  the environment and humans. In recent years many  researchers have established the use of supplementary  cementitious materials (SCM) like flyash (FA) not only  improves the various properties of concrete both in its fresh  and hardened states but also can contribute to economic  construction costs. Plastic bags which are commonly used  for packing, carrying vegetables, etc create a serious  environmental problem. The safe disposal of plastic bags in  the environment is the most challenging issue for solid  waste management across the globe. These are non biodegradable and toxic. Every year at least 15% of total  plastic waste remains untreated. Concrete is one of the best  choices for construction in many countries today. Waste  plastic is being tried in the field of construction as a spatial  replacement in fine aggregate, coarse aggregate, or as an  additive the concrete. In the present study fly ash (FA) is  taken as the partial replacement in cement and low-density  polyethylene (LDPE) is used as an additive in the concrete.  FA was partially replaced in cement at percentages of 10,  20, and 30. Along with the variation of FA, LDPE was also  added from 0.2% to 1% in the concrete by volume. Ample  number of samples in M20 grade was prepared with a w/c  ratio of 0.55 It was found from the result that the optimum  compressive strength for 7 days and 28 days were 28.44  N/mm2 and 33.77N/mm2 obtained at 20% percent  replacement of FA with 0.4% addition of LDPE Similarly  the optimum split tensile strength for 28 days was 2.49  N/mm2 obtained at 20% replacement of FA with 0.8%  addition of LDPE. Thus 20% FA with up to 0.4% LDPE  can be adopted so that the disposal of waste plastic and fly  ash can be done well as well and the efficiency of the  concrete can be managed effectively.
Keywords: Fly Ash; Waste Plastic; LDPE; M20 Grade Concrete; Compressive Strength; Split Tensile Strength